VD_FINDINFO HC / 2010 / 183 vom 13. Januar 2010 - VD Tribunal cantonal (2010)
MANDAT, RÉSILIATION EN TEMPS INOPPORTUN, DOMMAGE, FARDEAU DE LA PREUVE | 8 CC, 394 CO, 404 al. 1 CO, 404 al. 2 CO, 42 al. 2 CO, 451 ch. 4 CPC, 457 al. 1 CPC, 465 al. 1 CPC